2016
DOI: 10.1515/jppr-2016-0031
|View full text |Cite
|
Sign up to set email alerts
|

A study on controlling Setaria viridis and Corchorus olitorius associated with Phaseolus vulgaris growth using natural extracts of Chenopodium album

Abstract: The effects of water extracts of Chenopodium album leaves and roots on the growth of grass weed (Setaria viridis) and broad leaf weed (Corchorus olitorius) grown with beans (Phaseolus vulgaris) in greenhouse pots were studied in the National Research Centre, Giza, Egypt. In this experiment fresh leaf and root extracts and their corresponding dry leaf and root extracts at different concentrations were used. There were significant inhibitions in the dry weights of S. viridis and C. olitorius by all extracts at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…These results confirmed that phenols or flavonoids or both may be the cause of allelopathic inhibition. Different documented results confirmed these obtained results [25][26][27] . The results of TLC analysis (Thin Layer chromatography) indicated that total polyphenol contains tannin, gallic and chlorogenic acids in Table 6 and Fig.…”
Section: Results Of Analysis Of Leaf Root and Seed Extracts Ofsupporting
confidence: 82%
See 1 more Smart Citation
“…These results confirmed that phenols or flavonoids or both may be the cause of allelopathic inhibition. Different documented results confirmed these obtained results [25][26][27] . The results of TLC analysis (Thin Layer chromatography) indicated that total polyphenol contains tannin, gallic and chlorogenic acids in Table 6 and Fig.…”
Section: Results Of Analysis Of Leaf Root and Seed Extracts Ofsupporting
confidence: 82%
“…Thus, an increase in sunflower growth and yield may result from E. colonum control by different extracts of M. oleifera or enhancement effect. Several workers proved that increase in crop growth and yield was concomitant with controlling weeds 27,[38][39] . This study indicated inhibition in weed growth by the extracts of different parts of Moringa oleifera.…”
Section: Results Of Analysis Of Leaf Root and Seed Extracts Ofmentioning
confidence: 99%
“…The reducing effect of F. nitida leaf powder on the growth of both weeds, i.e., P. minor and M. parviflora, could be attributed to these natural allelochemicals. These results were confirmed by El-Rokiek et al (2016). Another confirming results were found also by some researcher that leaves and bark extracts of F. bengalensis have different allelopathic effect on seed germination percentage and early seedling growth parameters of some economic crop plants as maize (Zea mays), mung bean (Vigna radiata), and sunflower (Helianthus annuus), and these allelopathic effects are due to their allelochemicals mainly the total phenolic acids content that proportion to the concentration (Mohsin et al 2016;Muhammad et al 2018).…”
Section: Discussionsupporting
confidence: 65%
“…In an attempt to reduce environmental pollution and reduce the resistance of weeds to herbicides, several workers have controlled weeds in crop plants using natural extracts of different plants (Batish et al 2006;Cheema et al 2013;El-Rokiek et al 2016, 2018. The inhibition in weed growth by such natural extracts may be attributed to the presence of some causative allelochemicals (Chon et al 2003).…”
Section: Seed Qualitymentioning
confidence: 99%